(untitled) (Academicia Globe: Inderscience Research, 2021)
The article aims to discover and focus on responsible leadership. The problem is approached from the perspective of a dyadic relationship between managers and employees. Answers to the following study questions: What concepts do managers and employees believe are important in the manager–employee relationship for responsible leadership? What social conditions in the relationship necessitate the application of the principles?